Usability Evaluation of Grammar Learning Application Using SUS Method - Nurkholis, Galuh Ihsan; Mulyati, Sri (International Journal of Informatics and Computation, 2026)
We proposed a mobile English grammar learning application based on the Formula 33 method to support structured, rule-based grammar instruction in a Mobile Assisted Language Learning environment. Many existing mobile language learning applications provide rich content but do not ensure that users can effectively follow systematic grammar learning workflows, which often leads to interaction difficulties and reduced learning focus. The proposed application guided learners through sequential stages of sentence identification, temporal analysis, and formula construction, and integrated quizzes along with an interactive learning assistant to support grammar exploration. This study utilized the System Usability Scale (SUS) to evaluate perceived usability, involving 32 participants who completed guided learning tasks before responding to the questionnaire. The evaluation produced a mean SUS score of 73.3, indicating a “Good” rating and an acceptable usability level above the standard benchmark. The results showed that users were able to understand and operate the structured learning process with minimal assistance, although first-time users experienced slight initial complexity. These findings demonstrate that an explicit, rule-based grammar learning approach can be effectively implemented in a mobile learning environment without introducing significant usability barriers.